Mfn2 Protects Dopaminergic Neurons Exposed to Paraquat Both in vitro and in vivo: Implications for Idiopathic Parkinson’s Disease - Zhao, Fanpeng (Biochim Biophys Acta, 2017)
Mitochondrial dynamics and quality control plays a critical role in the maintenance of mitochondrial homeostasis and function. Pathogenic mutations of many genes associated with familial Parkinson’s disease (PD) caused abnormal mitochondrial dynamics, suggesting a likely involvement of disturbed mitochondrial fission/fusion in the pathogenesis of PD. In this study, we focused on the potential role of mitochondrial fission/fusion in idiopathic PD patients and in neuronal cells and animals exposed to paraquat (PQ), a commonly used herbicide and PD-related neurotoxin, as models for idiopathic PD. Significantly increased expression of dynamin-like protein 1 (DLP1) and a trend towards reduced expression of Mfn1 and Mfn2 were noted in the substantia nigra tissues from idiopathic PD cases. Interestingly, PQ treatment led to a similar changes in the expression of fission/fusion proteins both in vitro and in vivo which was accompanied by extensive mitochondrial fragmentation and mitochondrial dysfunction. Blockage of PQ-induced mitochondrial fragmentation by Mfn2 overexpression protected neurons against PQ-induced mitochondrial dysfunction in vitro. More importantly, PQ-induced oxidative damage and stress signaling as well as selective loss of dopaminergic (DA) neurons in the substantia nigra and axonal terminals in striatum was also inhibited in transgenic mice overexpressing hMfn2. Overall, our study demonstrated that disturbed mitochondrial dynamics mediates PQ-induced mitochondrial dysfunction and neurotoxicity both in vitro and in vivo and is also likely involved in the pathogenesis of idiopathic PD which make them a promising therapeutic target for PD treatment.